Zmienność ładunków zawiesiny ogólnej w ściekach odprowadzanych kanalizacją deszczową na przykładzie wybranej zlewni = The variability of total suspended solids in storm water in the example of a chosen catchment - Górska, Katarzyna; Sikorski, Mikołaj (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the most important parameters, in assessing the contamination degree of rainwater from urban catchments is a total suspension. The number of suspensions of these sewages is highly variable and depends on many factors. They are related mainly to the development of catchments. The aim of the article is to compare the variation of freshet levels and loads of total suspended solids in a specific wave of rain and snowmelt, which are observed in the urban catchment in Kielce.
Keywords: ścieki deszczowe; zawiesina ogólna; wezbranie; rain water; total suspension; raised water